Requirements analysis strategy for the development of augmented reality environments - Nakamoto, Paula Teixeira (2012)
Augmented Reality (AR) offers the advantage of enabling the use of tangible actions and multimodal operations, including voice, gestures, and touch, among others. Due to the its interface varieties of interfaces, the complexity in designing and using them is notably high. Therefore, this system´s designers need to develop a user-focused project or else a lot of usability problems may arise. In order to solve these problems, AR environment designers need instructions, guidance and guidelines in order to help them develop a project. So far, AR project instructions, found in the related literature, are very limited, stemming from researchers' specific problems. This paper has the purpose of presenting an investigation that resulted in a Requirements Analysis Strategy for the development of AR environments. As a result of this strategy, guiding designers have at their disposal domain analysis activities and forms that help them analyze requirements and make decisions on how to proceed in the system´s implementation. The strategy efficacy is verified by means of its application to a requirements specification meta model for the development of a system that helps in the treatment of arachnophobia.